HARMONY OF RELIGIOUS DIVERSITY IN BANYUMAS - Ulul Huda; Iis Sugiarti (Program Studi Pendidikan Bahasa Inggris Fakultas ilmu Budaya, 2023)
This research focuses on community interaction that creates an attitude of tolerance so that it has implications for the realization of religious harmony in Banyumas. The specific objective of this research is to discover the heterogeneous interaction patterns of the Banyumas community and to reveal the involvement of organizations and communities that intersect with issues of tolerance in creating a conducive religious atmosphere in Banyumas. This type of research is field research with a qualitative research approach and the nature of this research is descriptive analytic. As for data collection techniques using interviews, observation and documentation. The results of the study show that: 1) the interaction patterns of the Banyumas people who are diverse in terms of religion are quite harmonious because they are supported by the character of the Banyumas people who are egalitarian and inclusive. Local wisdom values is also still held tightly by the people of Banyumas, so that it has implications for the harmony of diversity in Banyumas, even though there is still frictional religious relations and there are ideological tendencies; 2) the involvement of religious institutions or communities in realizing religious harmony, FKUB Banyumas in this case has a significant contribution, besides that it is endeavored by each religious element from Islam, Christianity, Catholicism, Confucianism, Hinduism, Buddhism through their respective religious communities. In the context of an interfaith community, FORSA Banyumas consistently disseminates messages of harmony, especially to students and the younger generation. Keywords: Diversity, Harmony, Religious, Communities in Banyumas